2010
DOI: 10.1111/j.1365-2117.2009.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Emplacement mechanics of sandstone intrusions: insights from the Panoche Giant Injection Complex, California

Abstract: The Panoche Giant Injection Complex (PGIC; California) constitutes the most complete sandstone intrusion network yet described, and is an excellent analogue for subsurface hydrocarbon reservoirs modified by sand remobilisation. Sandstone dykes and sills were intruded during the Late Palaeocene into slope mudstones of the Great Valley forearc basin, and are exposed for more than 300 km2. The PGIC consists of dykes and sills and represents upwards infilling of natural hydraulic fractures sourced from highly over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 63 publications
(173 reference statements)
4
47
0
Order By: Relevance
“…It has been applied in several studies of dyke emplacement (e.g. Baer and Beyth, 1990;Riley et al, 2005;Vétel and Cartwright, 2010;Martínez-Poza et al, 2014).…”
Section: Analysis Of Dyke Net Dilation Directionmentioning
confidence: 98%
“…It has been applied in several studies of dyke emplacement (e.g. Baer and Beyth, 1990;Riley et al, 2005;Vétel and Cartwright, 2010;Martínez-Poza et al, 2014).…”
Section: Analysis Of Dyke Net Dilation Directionmentioning
confidence: 98%
“…For decades, numerous networks of sand injectites in sedimentary basins worldwide have either been interpreted from seismic data (Timbrell, 1993;MacLeod et al, 1999;Lonergan et al, 2000;Molyneux et al, 2002;Huuse and Mickelson, 2004;Huuse et al, , 2007De Boer et al, 2007;Jackson, 2007Jackson, , 2011Szarawarska et al, 2010) or directly observed in the field (Truswell, 1972;Hiscott, 1979;Surlyk et NoeeNygaard, 2001;Fri es and Parize, 2003;Hubbard et al, 2007;V etel and Cartwright, 2009;Kane, 2010). Because the emplacement of clastic sills and dykes depends on many parameters such as the nature of fluids, the host rock properties, the nature of sand from the source, the depth of the sand source, and the process of injection, each sand injectite network is considered as unique in terms of its dimensions, the geometry of the network, and the distribution, density and orientation of injected sands.…”
Section: Introductionmentioning
confidence: 98%
“…); their length ranges from a few meters to 150 m (500 ft). They are characterized by abundant en echelon segmentation ( Figure 6A), a characteristic described as common in the area by Vétel and Cartwright (2010). …”
Section: Geometrymentioning
confidence: 99%
“…We propose the following hypotheses for the mechanisms of expulsion and migration of methane (Figures 14, 15). Vétel and Cartwright (2010) described the mechanism of depressurization of an injectite network after its emplacement as follows: from an initial pressure above the minimum stress (s min ), the critical value necessary for maintaining an open fracture, pressure rapidly decreases by pervasive fluid infiltration into the pore space of the host sediment or by connection to another permeable sand body or to the surface. In outcrops A and B, the tips of the dykes reached a depth very close to the sea floor and may even have erupted locally as sand volcanoes (Vigorito et al, 2008).…”
Section: Expulsion Mechanisms and Gas Migration Pathwaymentioning
confidence: 99%
See 1 more Smart Citation